PELATIHAN PENINGKATAN KUALITAS DIRI MAHASISWA DENGAN PUBLIC SPEAKING DI ERA 4.0 - Indrapuri, R. Sri Ayu; Annisa, Aulia; Yoshandi, T. Mohd; Sufanda, Zerry (LPPM Universitas Awal Bros, 2023)
Public speaking is one of the absolute abilities needed in the global 4.0 era, especially students. This is certainly triggered by the demands of the times and technology that exists today which forces individuals to be able to compete and improve their quality.. The purpose of this research activity is to help students improve their skills in public speaking, especially learning how to speak by influencing and motivating others in a professional context. This training is an effort to help students practice their skills in public speaking and also to improve the quality of their effective communication both for academic learning within the university and also for their preparation to be able to compete in the world of work in the future . The methods used in this training are lectures, demonstrations of ways how to influence and motivate others in a professional context and question and answer. The target of this training is students. The result of this training is that students can improve their ability in public speaking, especially being able to influence and motivate others in professional context Keywords: Public Speaking, Students, Era 4.0